Undernutrition and associated factors among internally displaced lactating mothers in Sekota camps, northern Ethiopia: A cross-sectional study - Mengstie, Misganaw Asmamaw; Worke, Mulugeta Dile; Belay, Yalemshet; Chekol Abebe, Endeshaw; Asmamaw Dejenie, Tadesse; Abdu Seid, Mohammed; Azezew, Muluken Teshome (Frontiers in Nutrition, 2023)
Background: Undernutrition is the term used to describe when a person consumes insufficient amounts of nutrients and energy to meet their needs for maintaining health. Despite substantial progress, undernutrition remains a serious public health concern in many low and middle-income nations, including Ethiopia. Women and children are, in reality, the most nutritionally vulnerable individuals, particularly in times of crisis. In Ethiopia, twenty-seven percent of lactating women are thin or malnourished, and 38% of children are stunted. Although the issue of undernutrition may worsen in times of emergency, like war, there are limited studies available in Ethiopia that show the nutritional status of lactating mothers in humanitarian settings. Objectives: The main aim of this study was to determine the prevalence and investigate the factors associated with undernutrition among internally displaced lactating mothers in Sekota camps, in northern Ethiopia. Methods: A cross-sectional study through a simple random sampling technique was conducted among 420 randomly selected lactating mothers in Sekota Internally Displaced Persons (IDP) camps. Data were collected using a structured questionnaire and anthropometric measurements. Logistic regression analysis was employed to identify independent factors associated with maternal undernutrition. Results: Using a cut-off mid-upper arm circumference < 23 cm, the prevalence of undernutrition among internally displaced lactating mothers was 54.8%. Large family size (adjusted odds ratio (AOR) = 4.35; 95% CI: 1.32, 10.22), short birth interval (AOR = 4.85; 95% CI: 1.24, 10.00), low maternal daily meal frequency (AOR = 2.54; 95% CI: 1.12, 5.75), and low dietary diversity score (AOR = 1.79; 95% CI: 1.03, 3.10) were all significantly associated with undernutrition. Conclusion: The prevalence of undernutrition among internally displaced lactating mothers is relatively high. Governments and other concerned organizations involved in providing care and support to Sekota IDP camps should increase their efforts to improve the nutritional status of lactating mothers